Investigation of documentation processes of students with low and high level of mathematical literacy: A case study - Kübra Ada; Menekşe Seden Tapan Broutin; Gül Kaleli Yılmaz; Gül Mine Bayram (Journal of Pedagogical Research, 2021)
The aim of this study is to analyze and compare the documentation processes of students with low and high mathematical literacy levels. To this aim, a qualitative research design was adopted. Participants in this case study consisted of two students studying at the 9th grade who were selected through the criterion sampling method considering the mathematical literacy levels (low and high). The participants were asked to draw and explain a schematic representation of the resource system that they employed in their mathematics learning process. They also completed 30-day mathematics learning diaries, which required them to explain the activities they did and the resources they used. Interviews were scheduled as the secondary data collection tool. Both content analysis and descriptive analysis were used to analyze the data. As a result, differences in resource usage schemes were found in the mathematics learning processes of two the participants. Compare to the student with low mathematical literacy, the objective of the action component of the utilization scheme for the student with high mathematical literacy was determined to be to associate mathematical knowledge with daily-life.